Saliva‑Based Diagnostics: Applications, Limitations and Future Prospects in Systemic Disease Detection: A Review - Haider Fadhil, Saja; Muayad Khudhair, Hiba (Kerbala Journal of Nursing and Health Sciences., 2025)
The accessibility of collection, cost-effectiveness, and ability to mirror systemic physiological and pathophysiological conditions have rendered saliva an attractive non-invasive diagnostic medium. It contains many potential biomarkers, such as proteins, enzymes, hormones, metabolites, and nucleic acids, which can provide significant information about endocrine disorders, cardiovascular diseases, viral infections, autoimmune diseases, cancer, and genetic defects. This up-to-date review focuses on the types of existing salivary biomarkers, their clinical utilities, diagnostic impact, and recent technical advances reported in studies published between 2018 and 2025. Original articles and review papers were included to discover trends, challenges and possible future directions of saliva-based diagnostics. These findings suggest salivary diagnostics can attain sensitivity and specificity comparable with classical methods, enabling early detection, disease monitoring, and therapeutic recommendations. Despite problems of variability, collection methods and standardization, saliva-based diagnostics have vast potential for clinical utility. Additional investigation is expected to enhance their reliability and clinical application in systemic disease diagnosis.